Addressing Reproductive Justice in Midwifery: Insights from Eastern Indonesia - Herbawani, Chahya Kharin; Kristianingrum , Ika Ayu (LPPM Universitas Prima Nusantara Bukittinggi, 2026)
Background: Reproductive justice links reproductive rights with social justice, highlighting how systemic inequalities shape reproductive autonomy. Midwives, especially in underserved areas, are frontline advocates who provide clinical care, emotional support, and community advocacy aligned with this framework. Purpose: This study explores midwives’ experiences in responding to requests for assistance with unwanted pregnancy termination, a central issue in reproductive justice. Methods: A community service approach was used through Focus Group Discussions (FGDs) in Sorong, Southwest Papua, Indonesia. Fifteen midwives from rural and peri-urban health facilities participated. The FGDs aimed to understand their dual roles as healthcare providers and advocates for women’s reproductive rights. Results: Findings show midwives in Eastern Indonesia are key actors in advancing reproductive rights by offering vital reproductive health services and supporting marginalized women. However, their ability is hindered by barriers such as limited knowledge of regulations, lack of resources, cultural stigma, and restrictive policies. These challenges restrict their capacity to address reproductive justice issues effectively. Conclusion: The study highlights the urgent need to integrate reproductive justice principles into midwifery education and training. Equipping midwives with knowledge, advocacy tools, and policy awareness will strengthen their role in protecting women’s reproductive rights in low-resource settings. This research adds to global discussions on reproductive justice and underscores the transformative potential of midwifery practice in advancing health equity in Eastern Indonesia.